STUDY ON THE TRANSPORT SYSTEM OF FEEDSTOCK IN AGRICULTURAL BIOGAS PLANTS - Mariana DUMITRU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The human energetic necessities are frequently exceeded by the energetic potential of plants, but the present technologies use only a small part of biomass to be used for transforming it in energy. Even so, the energy obtained from biomass obtained from agriculture, forests and waste can be significant. In this respect, biogas is an important biofuel and biogas plants represent a good resource of energy, which can be used both in rural and urban communities. The paper refers to the first stage of an agricultural biogas plant, transport, delivery and storage of feedstock. Thus, stackable feedstock like grass, maize silage, manure with high straw content, vegetable residues, must be transported from a storage facility, such as a bunker silo to the digester feeding system. This is usually done by loaders or tractors and the feedstock is fed into the digester using different transporting systems, which are analysed in this paper.